Electrochemical device and electronic device
By adding specific additives to the positive electrode active material layer of the lithium-ion battery and controlling its content, the problem of reduced capacity during the circulation of the lithium-ion battery is solved, and the cycling performance and DC impedance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411741825.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-05
- Publication Date
- 2025-03-18
AI Technical Summary
During the cycle of lithium-ion batteries, the charging/discharging capacity will decrease, resulting in a decrease in performance, and poor raw material matching during the preparation process will lead to difficulty in batching.
By adding additives with hydrophilic groups and lipophilic groups to the positive electrode active material layer, and controlling the content of the additives and the content of the compound of formula 1 in the electrolyte, the contact angle of the positive electrode active material layer is not greater than 45°, thereby improving interface stability.
The circulation performance, rate performance and DC impedance of lithium-ion batteries have been significantly improved, and the overall performance of electrochemical devices has been improved.
Smart Images

Figure BDA0005162763490000021 
Figure BDA0005162763490000022 
Figure BDA0005162763490000121
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application submitted to the China Patent Office on January 7, 2022, with application number 202080049701.8 and invention name “Electrochemical Device and Electronic Device”. Technical Field
[0002] The present application relates to the field of energy storage, and in particular to an electrochemical device and an electronic device, in particular a lithium-ion battery. Background Art
[0003] With the development of technology and the increase in demand for mobile devices, people's demand for electrochemical devices (such as lithium-ion batteries) has increased significantly, thereby placing higher requirements on the performance of lithium-ion batteries, especially the cycle performance of lithium-ion batteries.
[0004] During the cycle, the charge / discharge capacity of lithium-ion batteries will decrease, thus reducing the performance of lithium-ion batteries. The performance of lithium-ion batteries mainly depends on the characteristics of electrodes, electrolytes and separators. The performance of electrodes depends not only on the characteristics of the current collector and the active material layer, but also on the additives in the active material layer. The additives help disperse the particles in the active material layer or bond the interface. However, in the preparation process of lithium-ion batteries, problems such as difficulty in mixing ingredients due to poor matching of raw materials are often encountered, which will have an adverse effect on the performance of lithium-ion batteries.
[0005] In view of the above, there is a real need to provide an electrochemical device and an electronic device with improved performance. Summary of the invention
[0006] The embodiments of the present application provide an electrochemical device and an electronic device to solve at least one problem existing in the related art to at least some extent.
[0007] In one aspect of the present application, the present application provides an electrochemical device comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode active material layer, wherein the contact angle of the positive electrode active material layer relative to a non-aqueous solvent is not greater than 45° as measured by a contact angle measurement method.
[0008] According to an embodiment of the present application, the contact angle measurement method refers to adding a 3 μl drop of diethyl carbonate to the surface of the positive electrode active material layer and then testing the contact angle of the drop on the surface of the positive electrode active material layer within 100 seconds.
[0009] According to an embodiment of the present application, the positive electrode active material layer includes an auxiliary agent having a hydrophilic group and a lipophilic group.
[0010] According to an embodiment of the present application, the auxiliary agent has at least one of the following characteristics:
[0011] (a) The oxidation potential is not less than 4.5 V and the reduction potential is not greater than 0.5 V;
[0012] (b) The surface tension is not greater than 40 mN / m;
[0013] (c) including unsaturated carboxyl groups;
[0014] (d) The content of the auxiliary agent is not more than 3000 ppm based on the total weight of the positive electrode active material layer.
[0015] According to an embodiment of the present application, the auxiliary agent includes at least one of 2-dodecyl acrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate, (2-ethylhexyl) acrylate, acrylate non-ionic fluorocarbon surfactant, dodecyl methacrylate, dodecyl methacrylate, acrylic acid (ester) copolymer, maleic acid acrylic acid copolymer or ethylene acrylic acid copolymer.
[0016] According to an embodiment of the present application, the electrolyte comprises a compound of formula 1:
[0017]
[0018] Wherein R is substituted or unsubstituted C 1 -C 10 a hydrocarbon group, and when substituted, the substituent is a halogen,
[0019] The content of the compound of Formula 1 is 0.001 wt % to 2 wt % based on the total weight of the electrolyte.
[0020] According to an embodiment of the present application, the compound of formula 1 comprises at least one of the following structural formulas:
[0021]
[0022] According to an embodiment of the present application, the content X mg of the compound of Formula 1 in the electrolyte and the reaction area Y m of the positive electrode active material layer 2 The following relationship is satisfied: 10≤X / Y≤100.
[0023] According to an embodiment of the present application, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a lithium-containing transition metal oxide with different median particle sizes.
[0024] According to an embodiment of the present application, the lithium-containing transition metal oxide includes a compound represented by general formula (1):
[0025] Li a M1 b M2 c M3d O 2 (1)
[0026] in:
[0027] M1 is selected from at least one of Co, Ni or Mn;
[0028] M2 is at least one selected from Mg, Ti, Zr, Ge, Nb, Al and Sn;
[0029] M3 is an element other than Li, M1 and M2;
[0030] 0.5≤a<1.1;
[0031] 0.8≤b<1.2;
[0032] 0.002≤c≤0.05; and
[0033] 0≤d≤0.05.
[0034] According to an embodiment of the present application, the lithium-containing transition metal oxide includes Mg and at least one metal element selected from Ti, Zr, Ge, Nb, Al and Sn.
[0035] In another aspect of the present application, the present application provides an electronic device, which includes the electrochemical device according to the present application.
[0036] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0037] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0038] Unless expressly stated otherwise, the following terms used herein have the meanings indicated below.
[0039] In the detailed description and claims, a list of items connected by the term "at least one of" may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements. The term "at least one of" has the same meaning as the term "at least one of."
[0040] The electrodes (positive or negative electrodes) of electrochemical devices (e.g., lithium-ion batteries) are usually prepared by mixing active materials, conductive agents, thickeners, binders, and solvents, and then applying the mixed slurry to a current collector. However, the matching between the solvent and the binder or between the solvent and the active material is usually poor, making the batching difficult. In addition, the theoretical capacity of the electrochemical device may vary with the type of active material. As the cycle proceeds, the electrochemical device usually produces a phenomenon of reduced charge / discharge capacity. This is because the electrode interface of the electrochemical device changes during the charging and / or discharging process. The interface includes the interface between the electrode and the electrolyte, the interface between the current collector and the electrode, and the interface between the electrode active material and the additive. Reduced interfacial stability can cause the electrode active material to fail to perform its function.
[0041] The present application ensures the interfacial stability of the electrochemical device during the cycle by using a specific positive electrode material, thereby improving the cycle performance, rate performance and DC impedance of the electrochemical device. The specific positive electrode material of the present application is achieved by controlling the contact angle on the surface of the positive electrode active material layer. As a method for controlling the contact angle, it can be controlled by adding an additive to the positive electrode slurry or providing an additive coating on the surface of the positive electrode active material layer.
[0042] The present application provides an electrochemical device, which includes a positive electrode, a negative electrode and an electrolyte as described below.
[0043] I. Positive electrode
[0044] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on one or both surfaces of the positive electrode current collector.
[0045] Positive electrode active material layer
[0046] The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer may be one layer or multiple layers, and each layer of the multiple layers of positive electrode active material may contain the same or different positive electrode active materials.
[0047] Contact Angle
[0048] A feature of the electrochemical device of the present application is that the contact angle of the positive electrode active material layer relative to the non-aqueous solvent is not greater than 45° as measured by the contact angle measurement method. In some embodiments, the contact angle of the positive electrode active material layer relative to the non-aqueous solvent is not greater than 40° as measured by the contact angle measurement method. In some embodiments, the contact angle of the positive electrode active material layer relative to the non-aqueous solvent is not greater than 35° as measured by the contact angle measurement method. When the positive electrode active material layer has a contact angle as described above relative to the non-aqueous solvent, the interface of the positive electrode active material layer has a suitable surface tension, good infiltration of the electrolyte, good stability in the charge and discharge cycle of the electrochemical device, and can significantly improve the cycle performance, rate performance and DC impedance of the electrochemical device.
[0049] The contact angle of the positive electrode active material layer relative to the non-aqueous solvent can reflect the surface properties of the positive electrode active material layer, which is one of the physicochemical parameters that characterize the positive electrode active material layer. The smaller the contact angle, the smaller the surface tension of the positive electrode active material layer, which can significantly improve the cycle performance, rate performance and DC internal resistance of the electrochemical device. The contact angle of the positive electrode active material layer relative to the non-aqueous solvent can be affected by many factors, mainly including additives.
[0050] In some embodiments, the contact angle measurement method refers to dropping a 3 μL drop of diethyl carbonate on the surface of the positive electrode active material layer and then measuring the contact angle of the drop on the surface of the positive electrode active material layer within 100 seconds.
[0051] The contact angle of the positive electrode active material layer relative to the non-aqueous solvent and the diameter of the non-aqueous solvent droplet can be measured by the following method: 3 microliters of diethyl carbonate is added to the surface of the positive electrode active material layer, and the droplet diameter is tested within 100 seconds using a JC2000D3E contact angle measuring instrument, and a 5-point fitting method (i.e., first take 2 points on the left and right planes of the droplet to determine the liquid-solid interface, and then take 3 points on the droplet arc) is used for fitting to obtain the contact angle of the positive electrode active material layer relative to the non-aqueous solvent. Each sample is measured at least 3 times, and at least 3 data with a difference of less than 5° are selected, and the average value is taken to obtain the contact angle of the positive electrode active material layer relative to the non-aqueous solvent.
[0052] The non-aqueous solvent used in the contact angle test can be selected from commonly used electrolyte solvents such as diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, methyl propyl carbonate or methyl isopropyl carbonate.
[0053] Additives
[0054] According to some embodiments of the present application, the positive electrode active material layer includes an auxiliary agent. In some embodiments, the auxiliary agent has a hydrophilic group and a lipophilic group.
[0055] In some embodiments, the oxidation potential of the auxiliary agent is not less than 4.5 V, and the reduction potential is not greater than 0.5 V. In some embodiments, the oxidation potential of the auxiliary agent is not less than 5 V, and the reduction potential is not greater than 0.3 V. The auxiliary agent with the above oxidation / reduction potential has stable electrochemical performance, which helps to improve the cycle performance, rate performance and DC impedance of the electrochemical device.
[0056] In some embodiments, the surface tension of the auxiliary agent is not more than 40mN / m. In some embodiments, the surface tension of the auxiliary agent is not more than 30mN / m. In some embodiments, the surface tension of the auxiliary agent is not more than 25mN / m. In some embodiments, the surface tension of the auxiliary agent is not more than 20mN / m. In some embodiments, the surface tension of the auxiliary agent is not more than 15mN / m. In some embodiments, the surface tension of the auxiliary agent is not more than 10mN / m. The surface tension of the auxiliary agent is measured under the condition of an auxiliary agent NMP solution with a solid content of 1%. The auxiliary agent having the surface tension as described above makes the positive electrode active material layer have a good interface, which helps to improve the cycle performance, rate performance and DC impedance of the electrochemical device.
[0057] The surface tension of the additive can be measured by the following method: Use JC2000D3E contact angle meter to test the additive NMP solution with a solid content of 1%, test each sample at least 3 times, select at least 3 data, take the average value, and obtain the surface tension of the additive.
[0058] In some embodiments, the auxiliary agent includes an unsaturated carboxylic acid group. In some embodiments, the unsaturated carboxylic acid group includes at least one of vinyl esters, vinyl chloride esters, acrylates, vinyl ether acrylates, butenoates, propiolates, butylates, or carboxylates modified with acrylamide, acrylonitrile, or vinyl ether groups.
[0059] In some embodiments, the auxiliary agent includes at least one of the following: 2-dodecyl acrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate, acrylate (2-ethylhexyl) ester, acrylate non-ionic fluorocarbon surfactant, dodecyl methacrylate, dodecyl methacrylate, acrylic acid (ester) copolymer, maleic acid acrylic acid copolymer or ethylene acrylic acid copolymer.
[0060] In some embodiments, the content of the auxiliary agent is no more than 3000ppm based on the total weight of the positive electrode active material layer. In some embodiments, the content of the auxiliary agent is no more than 2500ppm based on the total weight of the positive electrode active material layer. In some embodiments, the content of the auxiliary agent is no more than 2000ppm based on the total weight of the positive electrode active material layer. In some embodiments, the content of the auxiliary agent is no more than 1500ppm based on the total weight of the positive electrode active material layer. In some embodiments, the content of the auxiliary agent is no more than 1000ppm based on the total weight of the positive electrode active material layer. In some embodiments, the content of the auxiliary agent is no more than 500ppm based on the total weight of the positive electrode active material layer. In some embodiments, the content of the auxiliary agent is no more than 200ppm based on the total weight of the positive electrode active material layer. When the content of the auxiliary agent is within the above range, it helps to improve the cycle performance, rate performance and DC impedance of the electrochemical device.
[0061] Positive active material
[0062] There is no particular limitation on the type of positive electrode active material, as long as it can electrochemically absorb and release metal ions (e.g., lithium ions). In some embodiments, the positive electrode active material is a material containing lithium and at least one transition metal. Examples of positive electrode active materials may include, but are not limited to, lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds.
[0063] In some embodiments, the positive electrode active material includes lithium-containing transition metal oxides with different median particle sizes. In some embodiments, the lithium-containing transition metal oxides with different median particle sizes have the same or different chemical compositions.
[0064] In some embodiments, the lithium-containing transition metal oxide includes a compound represented by general formula (1):
[0065] Li a M1 b M2 c M3 d O 2 (1)
[0066] in:
[0067] M1 is selected from at least one of Co, Ni or Mn;
[0068] M2 is at least one selected from Mg, Ti, Zr, Ge, Nb, Al and Sn;
[0069] M3 is an element other than Li, M1 and M2;
[0070] 0.5≤a<1.1;
[0071] 0.8≤b<1.2;
[0072] 0.002≤c≤0.05; and
[0073] 0≤d≤0.05.
[0074] In some embodiments, M1 includes at least one of Co or Ni. When M1 includes at least one of Co or Ni, the content of at least one of Co or Ni in the lithium-containing transition metal oxide is not less than 50 mol %; in some embodiments, not less than 60 mol %; in some embodiments, not less than 70 mol %; in some embodiments, not less than 80 mol %; or in some embodiments, not less than 90 mol %.
[0075] In some embodiments, M1 includes Co. In some embodiments, M1 is Co. When M1 includes Co, the content of Co in the lithium-containing transition metal oxide is not less than 30 mol %; in some embodiments, not less than 50 mol %; in some embodiments, not less than 65 mol %; in some embodiments, not less than 80 mol %; in some embodiments, not less than 90 mol %; or in some embodiments, not less than 95 mol %. When the lithium-containing transition metal oxide includes Co, it helps to increase the density of the positive electrode active material layer. When the content of Co in the lithium-containing transition metal oxide is within the above range, the density of the positive electrode active material layer can be further improved.
[0076] In some embodiments, M2 includes Mg. In some embodiments, the content of Mg is not less than 0.01 mol% relative to the content of M1. In some embodiments, the content of Mg is not less than 0.05 mol% relative to the content of M1. In some embodiments, the content of Mg is not less than 0.07 mol% relative to the content of M1. In some embodiments, the content of Mg is not more than 0.5 mol% relative to the content of M1. In some embodiments, the content of Mg is not more than 0.2 mol% relative to the content of M1. In some embodiments, the content of Mg is not more than 0.1 mol% relative to the content of M1. In some embodiments, the content of Mg is within the range consisting of any two of the above endpoints relative to the content of M1. When the content of Mg in the lithium-containing transition metal oxide is within the above range, the Mg element can effectively play a role in improving the cycle performance, rate performance and DC impedance of the electrochemical device.
[0077] In some embodiments, M2 further includes at least one of Ti, Zr, Ge, Nb, Al, and Sn.
[0078] In some embodiments, M2 further includes at least one of Ti, Zr, Ge, or Nb. In some embodiments, the content of at least one of Ti, Zr, Ge, or Nb is not less than 0.005 mol% relative to the content of M1. In some embodiments, the content of at least one of Ti, Zr, Ge, or Nb is not less than 0.008 mol% relative to the content of M1. In some embodiments, the content of at least one of Ti, Zr, Ge, or Nb is not less than 0.01 mol% relative to the content of M1. In some embodiments, the content of at least one of Ti, Zr, Ge, or Nb is not greater than 0.3 mol% relative to the content of M1. In some embodiments, the content of at least one of Ti, Zr, Ge, or Nb is not greater than 0.1 mol% relative to the content of M1. In some embodiments, the content of at least one of Ti, Zr, Ge, or Nb is not greater than 0.05 mol% relative to the content of M1. In some embodiments, the content of at least one of Ti, Zr, Ge, or Nb is within the range formed by any two of the above endpoints relative to the content of M1. When the content of at least one of Ti, Zr, Ge or Nb in the lithium-containing transition metal oxide is within the above range, it helps to further improve the cycle performance, rate performance and DC impedance of the electrochemical device.
[0079] In some embodiments, M2 further includes at least one of Al or Sn. In some embodiments, the content of at least one of Al or Sn is not less than 0.01 mol% relative to the content of M1. In some embodiments, the content of at least one of Al or Sn is not less than 0.05 mol% relative to the content of M1. In some embodiments, the content of at least one of Al or Sn is not less than 0.07 mol% relative to the content of M1. In some embodiments, the content of at least one of Al or Sn is not more than 0.5 mol% relative to the content of M1. In some embodiments, the content of at least one of Al or Sn is not more than 0.2 mol% relative to the content of M1. In some embodiments, the content of at least one of Al or Sn is not more than 0.1 mol% relative to the content of M1. In some embodiments, the content of at least one of Al or Sn is within the range consisting of any two of the above endpoints relative to the content of M1. When the content of at least one of Al or Sn in the lithium-containing transition metal oxide is within the above range, it helps to further improve the cycle performance, rate performance and DC impedance of the electrochemical device.
[0080] In some embodiments, 0.004≤c≤0.02. In some embodiments, 0.006≤c≤0.01. When c is within the above range, the cycle performance, rate performance and DC impedance of the lithium ion battery can be further improved.
[0081] The lithium-containing transition metal oxide can contain M2 in a variety of ways, which are not particularly limited. In some embodiments, M2 is present on the lithium-containing transition metal oxide particles. In some embodiments, M2 is uniformly solid-dispersed in the lithium-containing transition metal oxide. In some embodiments, M2 is concentrated in the lithium-containing transition metal oxide with a concentration distribution. In some embodiments, M2 forms a compound layer on the surface of the lithium-containing transition metal oxide.
[0082] In some embodiments, M3 includes at least one of the following elements: alkali metal elements other than Li, alkaline earth metal elements other than Mg, Group IIIa metal elements, Group IVb metal elements other than Ti and Zr, Group Vb metal elements other than Nb, Group VIb metal elements, Group VIIb metal elements other than Mn, Group VIII metal elements other than Co and Ni, Group Ib metal elements, Zn, Group IIIa metal elements other than Al, Group IVa metal elements other than Sn and Pb, P or Bi.
[0083] In some embodiments, M3 includes at least one of the following elements: Na, K, Rb, Be, Ca, Sr, Ba, Sc, Y, La, Hf, V, Ta, Cr, Mo, W, Tc, Re, Fe, Ru, Rh, Cu, Ag, Au, Zn, B, Ca, In, Si, P or Bi.
[0084] In some embodiments, the lithium-containing transition metal oxide does not contain M3 (ie, d=0).
[0085] In some embodiments, the lithium-containing transition metal oxide comprises LiNi 0.81 Co 0.16 Al 0.03 O 2 、LiNi 0.81 Co 0.16 Mg 0.03 O 2 、LiNi 0.81 Co 0.16 Si 0.03 O 2 、LiNi 0.81 Co 0.16 Ti 0.03 O 2 、LiCo 0.96 Ti 0.04 O 2 、LiCo 0.99 8 Mg 0.0008 Ti 0.0004 Al 0.0008 O 2 、LiCo 0.994 Mg0.0024 Ti 0.0012 Al 0.0024 O 2 、LiCo 0.9988 Mg 0.0008 Ti 0.0004 O 2 、LiCo 0.9964 Mg 0.0024 Ti 0.0012 O 2 or LiCo 0.334 Ni 0.33 Mn 0.33 Mg 0.0024 Ti 0.0012 Al 0.0024 O 2 At least one of .
[0086] The content of each element in the lithium-containing transition metal oxide can be obtained by inductively coupled plasma (ICP) analysis. The lithium content in the lithium-containing transition metal oxide can also be measured by other methods (for example, atomic absorption method). Specifically, accurately weigh about 5g of lithium-containing transition metal oxide, add it to a 200ml beaker, then add 100ml of aqua regia, heat and concentrate it to a liquid volume of 20-25ml, cool it, separate the solids with quantitative filter paper "No.5B" manufactured by Advantec, add the filtrate and washings to a 100ml volumetric flask and dilute it to constant volume, and use the sequential ICP analyzer "IPIS1000" manufactured by Nippon Jarrell-Ash Co., Ltd. of Japan to measure the element content.
[0087] In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not more than 99wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not more than 97.5wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not more than 97wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not more than 98wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not more than 95wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not less than 85wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not more than 90wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is not more than 92wt%. In some embodiments, based on the total weight of the positive electrode active material layer, the content of the lithium-containing transition metal oxide is within the range formed by any two of the above endpoints. When the content of the lithium-containing transition metal oxide in the positive electrode active material layer is within the above range, the positive electrode active material layer has high capacity and low resistance, and contributes to the formation of the positive electrode.
[0088] In some embodiments, the lithium-containing transition metal oxide comprises first particles and second particles, the first particles having a first median particle size, the second particles having a second median particle size, the first median particle size being smaller than the second median particle size.
[0089] In some embodiments, the first median particle size is 0.5 μm to 10 μm. In some embodiments, the first median particle size is 1 μm to 8 μm. In some embodiments, the first median particle size is 2 μm to 6 μm. In some embodiments, the second median particle size is 11 μm to 30 μm. In some embodiments, the second median particle size is 12 μm to 25 μm. In some embodiments, the second median particle size is 13 μm to 20 μm.
[0090] In some embodiments, the discharge capacity of the positive electrode active material is less than the chargeable capacity of the negative electrode active material to prevent unintentional precipitation of lithium metal on the negative electrode during charging.
[0091] The median particle size of the lithium-containing transition metal oxide can be adjusted by the following method: NaOH is added dropwise to an acidic aqueous solution of the transition metal element M1 to precipitate the hydroxide of M1. The hydroxide of M1 is fired to obtain the oxide of M1. The median particle size of the lithium-containing transition metal oxide can be controlled by controlling the precipitation time, the precipitate particle size, and the particle size of the fired oxide of M1.
[0092] In some embodiments, the discharge capacity of the positive electrode active material is less than the chargeable capacity of the negative electrode active material to prevent unintentional precipitation of lithium metal on the negative electrode during charging.
[0093] Density of the positive electrode active material layer
[0094] In some embodiments, the density of the positive electrode active material layer is not less than 3.5 g / cm 3 In some embodiments, the density of the positive electrode active material layer is not less than 3.6 g / cm 3 In some embodiments, the density of the positive electrode active material layer is not less than 3.8 g / cm 3 In some embodiments, the density of the positive electrode active material layer is not greater than 4.6 g / cm 3 In some embodiments, the density of the positive electrode active material layer is no greater than 4.4 g / cm 3 In some embodiments, the density of the positive electrode active material layer is no greater than 4.2 g / cm 3 In some embodiments, the density of the positive electrode active material layer is within the range formed by any two of the above endpoints. When the density of the positive electrode active material layer is within the above range, the positive electrode active material layer has good wettability, which helps to improve the performance of the electrochemical device.
[0095] The density of the positive electrode active material layer can be measured by the following method: cut the positive electrode with a certain area, use an electronic balance with a minimum scale of 1 mg to measure its weight W1, and use a micrometer with a minimum scale of 1 μm to measure the thickness T1 of the positive electrode. Peel off the positive electrode collector, use an electronic balance to measure its weight W2, and use a micrometer to measure the thickness T2 of the positive electrode collector. W1-W2 is recorded as the weight of the positive electrode active material layer, and T1-T2 is recorded as the thickness of the positive electrode active material layer. The volume of the positive electrode active material layer is calculated based on the thickness and area of the positive electrode active material layer, and then the density of the positive electrode active material layer is calculated based on the weight and volume of the positive electrode active material layer.
[0096] Thickness of positive electrode active material layer
[0097] In some embodiments, the thickness of the positive electrode active material layer is 30 μm to 200 μm. In some embodiments, the thickness of the positive electrode active material layer is 50 μm to 180 μm. In some embodiments, the thickness of the positive electrode active material layer is 80 μm to 150 μm. In some embodiments, the thickness of the positive electrode active material layer is 100 μm to 120 μm. In some embodiments, the thickness of the positive electrode active material layer is 30 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm or within a range consisting of any two of the above values.
[0098] The thickness of the positive electrode active material layer can be measured by the following method: cut the positive electrode and measure the thickness T1 of the positive electrode using a micrometer with a minimum scale of 1 μm. Peel off the positive electrode current collector and measure the thickness T2 of the positive electrode current collector using a micrometer. T1-T2 is recorded as the thickness of the positive electrode active material layer.
[0099] Conductive layer
[0100] In some embodiments, the positive electrode active material layer may further include a conductive layer, the conductive layer including a conductive agent. In some embodiments, the conductive layer does not contain a positive electrode active material. Examples of the conductive agent include, but are not limited to, graphite, carbon black, or acetylene black.
[0101] In some embodiments, the content of the conductive agent is not less than 1wt% based on the total weight of the positive electrode active material layer. In some embodiments, the content of the conductive agent is not less than 1.1wt% based on the total weight of the positive electrode active material layer. In some embodiments, the content of the conductive agent is not less than 1.2wt% based on the total weight of the positive electrode active material layer. In some embodiments, the content of the conductive agent is not more than 3wt% based on the total weight of the positive electrode active material layer. In some embodiments, the content of the conductive agent is not more than 2wt% based on the total weight of the positive electrode active material layer. In some embodiments, the content of the conductive agent is not more than 1.5wt% based on the total weight of the positive electrode active material layer. In some embodiments, the content of the conductive agent is within the range consisting of any two of the above values based on the total weight of the positive electrode active material layer. When the content of the conductive agent in the positive electrode active material layer is within the above range, it helps to improve the density and capacity of the positive electrode active material layer, thereby improving the cycle performance of the electrochemical device and reducing its load characteristics.
[0102] Adhesives
[0103] In some embodiments, the positive electrode active material layer includes a binder. Examples of the binder include, but are not limited to, polyvinylidene fluoride or polytetrafluoroethylene.
[0104] In some embodiments, the content of the binder is not less than 1wt% based on the total weight of the positive active material layer. In some embodiments, the content of the binder is not less than 1.3wt% based on the total weight of the positive active material layer. In some embodiments, the content of the binder is not less than 1.5wt% based on the total weight of the positive active material layer. In some embodiments, the content of the binder is not more than 4wt% based on the total weight of the positive active material layer. In some embodiments, the content of the binder is not more than 3wt% based on the total weight of the positive active material layer. In some embodiments, the content of the binder is not more than 2wt% based on the total weight of the positive active material layer. In some embodiments, the content of the binder is within the range of any two of the above values based on the total weight of the positive active material layer. When the content of the binder in the positive active material layer is within the above range, the positive active material layer has good adhesion to the positive current collector, avoiding the possibility of positive electrode powdering and falling off, thereby helping to improve the stability of the positive electrode.
[0105] Positive current collector
[0106] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, at least one of aluminum, aluminum alloy, nickel-plated aluminum, stainless steel, titanium or tantalum; carbon materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0107] There is no particular limitation on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the form of the positive electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip roll, metal plate, metal film, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the form of the positive electrode current collector may include, but is not limited to, carbon plate, carbon film, carbon cylinder, etc. In some embodiments, the positive electrode current collector is a metal film. In some embodiments, the metal film is mesh-shaped.
[0108] In some embodiments, the thickness of the positive electrode current collector is 8 μm to 20 μm. In some embodiments, the thickness of the positive electrode current collector is 10 μm to 18 μm. In some embodiments, the thickness of the positive electrode current collector is 12 μm to 15 μm. In some embodiments, the thickness of the positive electrode current collector is within the range of any two of the above values.
[0109] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode active material layer, the surface of the positive electrode current collector may include a conductive agent. Examples of the conductive agent may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver.
[0110] The preparation method of the positive electrode of the present application is not limited. For example, the positive electrode can be manufactured by the following method: two or more lithium-containing transition metal oxides with different median particle sizes are mixed in a certain weight ratio, a conductive agent and a binder are added as needed, and a solvent is added to obtain a positive electrode mixture slurry. The obtained positive electrode mixture slurry is coated on a positive electrode current collector (for example, aluminum foil), dried, and a positive electrode active material layer is formed. The positive electrode active material layer is applied to one or both surfaces of the positive electrode current collector, and a calendering step is performed as needed to obtain a positive electrode.
[0111] II. Electrolyte
[0112] The electrolyte used in the electrochemical device of the present application includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolyte used in the electrochemical device of the present application further includes an additive.
[0113] In some embodiments, the electrolyte comprises a compound of Formula 1:
[0114]
[0115] Wherein R is substituted or unsubstituted C 1 -C 10 The substituent is a halogen.
[0116] In some embodiments, the compound of Formula 1 comprises at least one of the following structural formulas:
[0117]
[0118] In some embodiments, based on the total weight of the electrolyte, the content of the compound of formula 1 is 0.001wt% to 2wt%. In some embodiments, based on the total weight of the electrolyte, the content of the compound of formula 1 is 0.01wt% to 1wt%. In some embodiments, based on the total weight of the electrolyte, the content of the compound of formula 1 is 0.05wt% to 0.5wt%. In some embodiments, based on the total weight of the electrolyte, the content of the compound of formula 1 is 0.1wt% to 0.3wt%. In some embodiments, based on the total weight of the electrolyte, the content of the compound of formula 1 is 0.001wt%, 0.005wt%, 0.01wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt% or in the range consisting of any two of the above values. When the content of the compound of formula 1 in the electrolyte is within the above range, it helps to further improve the cycle performance, rate performance and DC impedance of the lithium ion battery.
[0119] In some embodiments, the content of the compound of Formula 1 in the electrolyte X mg and the reaction area of the positive electrode active material layer Y m 2 Satisfies the following relationship: 10≤X / Y≤100. In some embodiments, X and Y satisfy the following relationship: 20≤X / Y<100. In some embodiments, X and Y satisfy the following relationship: 20≤X / Y<70. When X and Y meet the above relationship, it helps to further improve the cycle performance, rate performance and DC impedance of the lithium-ion battery.
[0120] The reaction area of the positive electrode active material layer can be measured by the following method: Use a surface area meter (fully automatic surface area measuring device manufactured by Okura Riken) to pre-dry the sample at 350°C for 15 minutes under nitrogen flow, and then use a nitrogen-helium mixed gas with a relative pressure value of nitrogen accurately adjusted to 0.3 relative to atmospheric pressure, and measure it by the nitrogen adsorption BET single-point method using the gas flow method. The specific surface area of the positive electrode active material layer is tested in this way. The specific surface area of the positive electrode active material layer refers to the specific surface area of the entire positive electrode active material layer containing the positive electrode active material and additives (binders, conductive agents, thickeners and fillers, etc.). Measure the weight of the positive electrode active material layer, that is, the total weight of the entire positive electrode active material layer containing the positive electrode active material and additives (binders, conductive agents, thickeners and fillers, etc.). Calculate the reaction area of the positive electrode active material layer by the following formula:
[0121] Reaction area=specific surface area of positive electrode active material layer×weight of positive electrode active material layer.
[0122] In some embodiments, the electrolyte further comprises any non-aqueous solvent known in the prior art that can be used as a solvent for the electrolyte.
[0123] In some embodiments, the non-aqueous solvent includes, but is not limited to, one or more of the following: cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.
[0124] In some embodiments, examples of the cyclic carbonate may include, but are not limited to, one or more of the following: ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate. In some embodiments, the cyclic carbonate has 3-6 carbon atoms.
[0125] In some embodiments, examples of the linear carbonates may include, but are not limited to, one or more of the following: dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate, etc. Examples of fluorine-substituted linear carbonates may include, but are not limited to, one or more of the following: bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate, and 2,2,2-trifluoroethyl methyl carbonate, etc.
[0126] In some embodiments, examples of the cyclic carboxylic acid ester may include, but are not limited to, one or more of the following: one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.
[0127] In some embodiments, examples of the chain carboxylic acid esters may include, but are not limited to, one or more of the following: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate, etc. In some embodiments, some hydrogen atoms of the chain carboxylic acid ester may be substituted by fluorine. In some embodiments, examples of fluorine-substituted chain carboxylic acid esters may include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate, etc.
[0128] In some embodiments, examples of the cyclic ether may include, but are not limited to, one or more of the following: tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl1,3-dioxolane, 4-methyl1,3-dioxolane, 1,3-dioxane, 1,4-dioxane and dimethoxypropane.
[0129] In some embodiments, examples of the chain ether may include, but are not limited to, one or more of the following: dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane and 1,2-ethoxymethoxyethane, etc.
[0130] In some embodiments, examples of the phosphorus-containing organic solvent may include, but are not limited to, one or more of the following: trimethyl phosphate, triethyl phosphate, dimethyl ethyl phosphate, diethyl methyl phosphate, ethylidene methyl phosphate, ethylidene ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphate, and tris(2,2,3,3,3-pentafluoropropyl) phosphate, etc.
[0131] In some embodiments, examples of the sulfur-containing organic solvent may include, but are not limited to, one or more of the following: sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be substituted by fluorine.
[0132] In some embodiments, the aromatic fluorine-containing solvent includes, but is not limited to, one or more of the following: fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.
[0133] In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, or ethyl acetate. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.
[0134] After adding chain carboxylic acid esters and / or cyclic carboxylic acid esters to the electrolyte, the chain carboxylic acid esters and / or cyclic carboxylic acid esters can form a passivation film on the electrode surface, thereby improving the capacity retention rate of the electrochemical device after intermittent charging cycles. In some embodiments, the electrolyte contains 1% to 60% of chain carboxylic acid esters, cyclic carboxylic acid esters and combinations thereof. In some embodiments, the electrolyte contains ethyl propionate, propyl propionate, γ-butyrolactone and combinations thereof, and the content of the combination is 1% to 60%, 10% to 60%, 10% to 50%, 20% to 50% based on the total weight of the electrolyte. In some embodiments, the electrolyte contains 1% to 60%, 10% to 60%, 20% to 50%, 20% to 40% or 30% of propyl propionate based on the total weight of the electrolyte.
[0135] In some embodiments, examples of the additive may include, but are not limited to, one or more of the following: fluorocarbonate, ethylene carbonate containing a carbon-carbon double bond, a compound containing a sulfur-oxygen double bond, and an acid anhydride.
[0136] In some embodiments, the content of the additive is 0.01% to 15%, 0.1% to 10%, or 1% to 5%, based on the total weight of the electrolyte.
[0137] According to an embodiment of the present application, based on the total weight of the electrolyte, the content of the propionate is 1.5 to 30 times, 1.5 to 20 times, 2 to 20 times, or 5 to 20 times that of the additive.
[0138] In some embodiments, the additive comprises one or more fluorocarbonates. During the charging / discharging of the lithium-ion battery, the fluorocarbonates can work together with the propionate to form a stable protective film on the surface of the negative electrode, thereby inhibiting the decomposition reaction of the electrolyte.
[0139] In some embodiments, the fluorinated carbonate has the formula C=O(OR 1 )(OR 2 ), where R 1 and R 2 Each is selected from an alkyl or halogenated alkyl group having 1 to 6 carbon atoms, wherein R 1 and R 2 At least one of them is selected from a fluoroalkyl group having 1 to 6 carbon atoms, and R 1 and R 2 Optionally together with the atoms to which it is attached, it forms a 5- to 7-membered ring.
[0140] In some embodiments, examples of the fluorinated carbonates may include, but are not limited to, one or more of the following: fluoroethylene carbonate, cis-4,4-difluoroethylene carbonate, trans-4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, and ethyl trifluoroethyl carbonate, etc.
[0141] In some embodiments, the additive comprises one or more ethylene carbonates containing carbon-carbon double bonds. Examples of the ethylene carbonates containing carbon-carbon double bonds may include, but are not limited to, one or more of the following: vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, fluoro vinylene carbonate, trifluoromethyl vinylene carbonate; vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1-ethyl-2-vinyl ethylene carbonate, 1-n-propyl-2-vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1,1-divinyl ethylene carbonate, 1,2-divinyl ethylene carbonate, 1,1-dimethyl-2-methylene ethylene carbonate and 1,1-diethyl-2-methylene ethylene carbonate, etc. In some embodiments, the ethylene carbonate containing carbon-carbon double bonds includes vinylene carbonate, which is easy to obtain and can achieve more excellent effects.
[0142] In some embodiments, the additive comprises one or more compounds containing sulfur-oxygen double bonds. Examples of the compounds containing sulfur-oxygen double bonds may include, but are not limited to, one or more of the following: cyclic sulfates, chain sulfates, chain sulfonates, cyclic sulfonates, chain sulfites, and cyclic sulfites.
[0143] Examples of the cyclic sulfate may include, but are not limited to, one or more of the following: 1,2-ethylene glycol sulfate, 1,2-propylene glycol sulfate, 1,3-propylene glycol sulfate, 1,2-butylene glycol sulfate, 1,3-butylene glycol sulfate, 1,4-butylene glycol sulfate, 1,2-pentanediol sulfate, 1,3-pentanediol sulfate, 1,4-pentanediol sulfate, 1,5-pentanediol sulfate, and the like.
[0144] Examples of the chain sulfate ester may include, but are not limited to, one or more of the following: dimethyl sulfate, ethyl methyl sulfate, diethyl sulfate, and the like.
[0145] Examples of the chain sulfonate may include, but are not limited to, one or more of the following: fluorosulfonates such as methyl fluorosulfonate and ethyl fluorosulfonate, methyl methanesulfonate, ethyl methanesulfonate, butyl dimethanesulfonate, methyl 2-(methylsulfonyloxy)propionate, and ethyl 2-(methylsulfonyloxy)propionate.
[0146] Examples of the cyclic sulfonate ester may include, but are not limited to, one or more of the following: 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3-fluoro-1-propylene-1,3-sultone, 1-Fluoro-2-propylene-1,3-sultone, 2-fluoro-2-propylene-1,3-sultone, 3-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone, 1,4-butanesultone, 1,5-pentanesultone, methylene methanedisulfonate and ethylene methanedisulfonate, etc.
[0147] Examples of the chain sulfite may include, but are not limited to, one or more of the following: dimethyl sulfite, ethyl methyl sulfite, diethyl sulfite, and the like.
[0148] Examples of the cyclic sulfite may include, but are not limited to, one or more of the following: 1,2-ethylene glycol sulfite, 1,2-propylene glycol sulfite, 1,3-propylene glycol sulfite, 1,2-butylene glycol sulfite, 1,3-butylene glycol sulfite, 1,4-butylene glycol sulfite, 1,2-pentanediol sulfite, 1,3-pentanediol sulfite, 1,4-pentanediol sulfite, 1,5-pentanediol sulfite, and the like.
[0149] In some embodiments, the additive comprises one or more anhydrides. Examples of the anhydrides may include, but are not limited to, one or more of cyclic phosphoric anhydride, carboxylic anhydride, disulfonic anhydride, and carboxylic acid sulfonic anhydride. Examples of the cyclic phosphoric anhydride may include, but are not limited to, one or more of trimethyl phosphoric acid cyclic anhydride, triethyl phosphoric acid cyclic anhydride, and tripropyl phosphoric acid cyclic anhydride. Examples of the carboxylic acid anhydride may include, but are not limited to, one or more of succinic anhydride, glutaric anhydride, and maleic anhydride. Examples of the disulfonic anhydride may include, but are not limited to, one or more of ethane disulfonic anhydride and propane disulfonic anhydride. Examples of the carboxylic acid sulfonic anhydride may include, but are not limited to, one or more of sulfobenzoic anhydride, sulfopropionic anhydride, and sulfobutyric anhydride.
[0150] In some embodiments, the additive is a combination of fluorocarbonic acid ester and ethylene carbonate containing carbon-carbon double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound containing sulfur-oxygen double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound with 2-4 cyano groups. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic carboxylic acid ester. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic phosphoric acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and sulfonic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid sulfonic acid anhydride.
[0151] The electrolyte is not particularly limited, and any substance known as an electrolyte can be used arbitrarily. In the case of a lithium secondary battery, a lithium salt is generally used. Examples of the electrolyte may include, but are not limited to, LiPF 6 , LiBF 4 、LiClO 4 、LiAlF 4 、LiSbF 6 、LiTaF 6 ,LiWF 7 Inorganic lithium salts such as LiWOF 5 Lithium tungstate, etc.; HCO 2 Li, CH 3 CO 2 Li, CH 2 FCO 2 Li, CHF 2 CO 2 Li, CF 3 CO 2 Li, CF 3 CH 2 CO 2 Li, CF 3 CF 2 CO 2 Li, CF 3 CF 2 CF 2 CO 2 Li, CF 3 CF 2 CF 2 CF 2 CO 2 Lithium carboxylates such as Li; FSO 3 Li, CH 3 SO 3 Li, CH 2 FSO 3 Li, CHF 2 SO3 Li, CF 3 SO 3 Li, CF 3 CF 2 SO 3 Li, CF 3 CF 2 CF 2 SO 3 Li, CF 3 CF 2 CF 2 CF 2 SO 3 Lithium sulfonate salts such as Li; LiN(FCO) 2 、LiN(FCO)(FSO 2 )、LiN(FSO 2 ) 2 、LiN(FSO 2 )(CF 3 SO 2 )、LiN(CF 3 SO 2 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide lithium、LiN(CF 3 SO 2 )(C 4 F 9 SO 2 ) and other lithium imide salts; LiC(FSO 2 ) 3 、LiC(CF 3 SO 2 ) 3 、LiC(C 2 F 5 SO 2 ) 3 Methylated lithium salts; (malonate) borate lithium salts such as bis(malonate) borate and difluoro(malonate) borate lithium salts; (malonate) phosphate lithium salts such as tris(malonate) phosphate, difluorobis(malonate) lithium phosphate, tetrafluoro(malonate) lithium phosphate; and LiPF 4 (CF 3 ) 2 、LiPF 4 (C 2 F 5 ) 2 、LiPF 4 (CF 3SO 2 ) 2 、LiPF 4 (C 2 F 5 SO 2 ) 2 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiBF 3 C 3 F 7 , LiBF 2 (CF 3 2. LiBF 2 (C 2 F 5 ) 2 , LiBF 2 (CF 3 SO 2 ) 2 , LiBF 2 (C 2 F 5 SO 2 ) 2 Fluorine-containing organic lithium salts; lithium oxalate borate salts such as lithium difluorooxalatoborate and lithium bis(oxalato)borate; lithium oxalate phosphate salts such as lithium tetrafluorooxalato phosphate, lithium difluorobis(oxalato)phosphate, and lithium tris(oxalato)phosphate.
[0152] In some embodiments, the electrolyte is selected from LiPF 6 、LiSbF 6 、LiTaF 6 、FSO 3 Li, CF 3 SO 3 Li、LiN(FSO 2 ) 2 、LiN(FSO 2 )(CF 3 SO 2 )、LiN(CF 3 SO 2 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide lithium、LiC(FSO 2 ) 3 、LiC(CF 3 SO 2 )3 、LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 、LiPF 3 (CF 3 ) 3 、LiPF 3 (C 2 F 5 ) 3 , lithium difluorooxalatoborate, lithium bis(oxalate)borate or lithium difluorobis(oxalato)phosphate, which help to improve the output power characteristics, high-rate charge and discharge characteristics, high-temperature storage characteristics and cycle characteristics of electrochemical devices.
[0153] The content of the electrolyte is not particularly limited as long as it does not impair the effect of the present application. In some embodiments, the total molar concentration of lithium in the electrolyte is greater than 0.3 mol / L, greater than 0.4 mol / L or greater than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within the range consisting of any two of the above values. When the electrolyte concentration is within the above range, there will not be too little lithium as a charged particle, and the viscosity can be kept within an appropriate range, thereby easily ensuring good conductivity.
[0154] When using two or more electrolytes, the electrolyte includes at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a salt selected from the group consisting of monofluorophosphate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a lithium salt. In some embodiments, based on the total weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is greater than 0.01wt% or greater than 0.1wt%. In some embodiments, based on the total weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is less than 20wt% or less than 10wt%. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is within the range consisting of any two of the above values.
[0155] In some embodiments, the electrolyte comprises one or more substances selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate and one or more salts other than these. As salts other than these, the lithium salts exemplified above can be cited, and in some embodiments, LiPF 6 、LiN(FSO 2 )(CF 3 SO 2 )、LiN(CF 3 SO 2 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide lithium、LiC(FSO 2 ) 3 、LiC(CF 3 SO 2 ) 3 、LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 、LiPF 3 (CF 3 ) 3 、LiPF 3 (C 2 F 5 ) 3 In some embodiments, the salt other than LiPF 6 .
[0156] In some embodiments, the content of the salt other than this is greater than 0.01wt% or greater than 0.1wt% based on the total weight of the electrolyte. In some embodiments, the content of the salt other than this is less than 20wt%, less than 15wt% or less than 10wt% based on the total weight of the electrolyte. In some embodiments, the content of the salt other than this is within the range consisting of any two of the above values. The salt other than this having the above content helps balance the conductivity and viscosity of the electrolyte.
[0157] In the electrolyte, in addition to the above-mentioned solvents, additives and electrolyte salts, additional additives such as negative electrode film forming agents, positive electrode protective agents, and anti-overcharge agents may be contained as needed. As additives, additives generally used in non-aqueous electrolyte secondary batteries can be used, examples of which may include, but are not limited to, vinylene carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroanisole, propane sultone, propene sultone, etc. These additives can be used alone or in any combination. In addition, the content of these additives in the electrolyte is not particularly limited, and can be appropriately set according to the type of the additive, etc. In some embodiments, based on the total weight of the electrolyte, the content of the additive is less than 5wt%, in the range of 0.01wt% to 5wt%, or in the range of 0.2wt% to 5wt%.
[0158] III. Negative electrode
[0159] The negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material layer, and the negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer can be one or more layers, and each layer of the multi-layer negative electrode active material can contain the same or different negative electrode active materials. The negative electrode active material is any substance that can reversibly embed and deintercalate metal ions such as lithium ions. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.
[0160] As a current collector for holding the negative electrode active material, any known current collector can be used. Examples of negative electrode current collectors include, but are not limited to, metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.
[0161] In the case where the negative electrode current collector is a metal material, the negative electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip, metal plate, metal film, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the negative electrode current collector is a metal film. In some embodiments, the negative electrode current collector is a copper foil. In some embodiments, the negative electrode current collector is a rolled copper foil based on a rolling method or an electrolytic copper foil based on an electrolytic method.
[0162] In some embodiments, the thickness of the negative electrode current collector is greater than 1 μm or greater than 5 μm. In some embodiments, the thickness of the negative electrode current collector is less than 100 μm or less than 50 μm. In some embodiments, the thickness of the negative electrode current collector is within a range consisting of any two of the above values.
[0163] There is no particular limitation on the negative electrode active material, as long as it can reversibly absorb and release lithium ions. Examples of negative electrode active materials may include, but are not limited to, carbon materials such as natural graphite and artificial graphite; metals such as silicon (Si) and tin (Sn); or oxides of metal elements such as Si and Sn. Negative electrode active materials may be used alone or in combination.
[0164] The negative electrode active material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0165] The negative electrode can be prepared by applying a negative electrode mixture slurry containing a negative electrode active material, a resin binder, etc. on a negative electrode current collector, drying it, and then rolling it to form a negative electrode active material layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.
[0166] IV. Isolation membrane
[0167] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.
[0168] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, glass filters, etc. In some embodiments, the material of the isolation membrane is a glass filter. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above-mentioned isolation membranes can be used alone or in any combination.
[0169] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.
[0170] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.
[0171] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators may also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.
[0172] The thickness of the isolation membrane is arbitrary. In some embodiments, the thickness of the isolation membrane is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the isolation membrane is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the isolation membrane is within the range consisting of any two of the above values. When the thickness of the isolation membrane is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.
[0173] When a porous material such as a porous sheet or non-woven fabric is used as an isolation membrane, the porosity of the isolation membrane is arbitrary. In some embodiments, the porosity of the isolation membrane is greater than 20%, greater than 35%, or greater than 45%. In some embodiments, the porosity of the isolation membrane is less than 90%, less than 85%, or less than 75%. In some embodiments, the porosity of the isolation membrane is within the range consisting of any two of the above values. When the porosity of the isolation membrane is within the above range, insulation and mechanical strength can be ensured, and membrane resistance can be suppressed, so that the electrochemical device has good rate characteristics.
[0174] The average pore size of the isolation membrane is also arbitrary. In some embodiments, the average pore size of the isolation membrane is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the isolation membrane is greater than 0.05 μm. In some embodiments, the average pore size of the isolation membrane is within the range consisting of any two of the above values. If the average pore size of the isolation membrane exceeds the above range, short circuit is likely to occur. When the average pore size of the isolation membrane is within the above range, the membrane resistance can be suppressed while preventing short circuit, so that the electrochemical device has good rate characteristics.
[0175] V. Electrochemical Device Components
[0176] The electrochemical device assembly includes an electrode group, a current collecting structure, an outer casing and a protective element.
[0177] Electrode Group
[0178] The electrode group may be any one of a stacked structure formed by stacking the above-mentioned positive electrode and the negative electrode with the above-mentioned separator, and a structure formed by spirally winding the above-mentioned positive electrode and the negative electrode with the above-mentioned separator. In some embodiments, the proportion of the mass of the electrode group in the internal volume of the battery (electrode group occupancy) is greater than 40% or greater than 50%. In some embodiments, the electrode group occupancy is less than 90% or less than 80%. In some embodiments, the electrode group occupancy is within the range consisting of any two of the above values. When the electrode group occupancy is within the above range, the capacity of the electrochemical device can be ensured, and at the same time, the reduction of repeated charge and discharge performance and high temperature storage characteristics associated with the increase in internal pressure can be suppressed, thereby preventing the gas release valve from working.
[0179] Current collection structure
[0180] There is no particular limitation on the current collection structure. In some embodiments, the current collection structure is a structure that reduces the resistance of the wiring portion and the joint portion. When the electrode group is the above-mentioned stacked structure, it is suitable to use a structure formed by bundling the metal core portions of each electrode layer and welding them to the terminal. When the electrode area increases, the internal resistance increases, so it is also suitable to set more than two terminals in the electrode to reduce the resistance. When the electrode group is the above-mentioned winding structure, the internal resistance can be reduced by setting more than two lead structures at the positive electrode and the negative electrode respectively, and bundling them at the terminal.
[0181] External shell
[0182] The material of the outer casing is not particularly limited, as long as it is a material that is stable to the electrolyte used. The outer casing can be made of, but not limited to, nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy and other metals, or a laminated film of resin and aluminum foil. In some embodiments, the outer casing is a metal or laminated film of aluminum or aluminum alloy.
[0183] The metal outer casing includes, but is not limited to, a packaged closed structure formed by welding metals to each other by laser welding, resistance welding, and ultrasonic welding; or a riveted structure formed by using the above-mentioned metals through a resin gasket. The outer casing using the above-mentioned laminated film includes, but is not limited to, a packaged closed structure formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above-mentioned resin layers. When the resin layer is thermally bonded to form a closed structure through the collector terminal, due to the bonding between the metal and the resin, a resin with a polar group or a modified resin into which a polar group is introduced can be used as the sandwiched resin. In addition, the shape of the outer casing is also arbitrary, for example, it can be any of cylindrical, square, laminated, button-shaped, large, etc.
[0184] Protection components
[0185] The protection element may be a positive temperature coefficient (PTC) whose resistance increases when abnormal heat is released or excessive current flows, a temperature fuse, a thermistor, or a valve (current cutoff valve) that cuts off the current flowing in the circuit by causing the internal pressure or internal temperature of the battery to rise sharply when abnormal heat is released. The above protection element may be selected to be an element that does not work in normal use of high current, or may be designed in a form that does not cause abnormal heat release or thermal runaway even if the protection element is not present.
[0186] VI. Application
[0187] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0188] The present application further provides an electronic device, which includes the electrochemical device according to the present application.
[0189] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0190] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.
[0191] Example
[0192] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.
[0193] 1. Preparation of lithium-ion batteries
[0194] 1. Preparation of negative electrode
[0195] Artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed with deionized water in a mass ratio of 96%:2%:2%, and stirred evenly to obtain negative electrode slurry. The negative electrode slurry was coated on a 12 μm copper foil. After drying, cold pressing, cutting and welding of the tabs, a negative electrode was obtained.
[0196] 2. Preparation of positive electrode
[0197] The positive electrode active material, conductive material (Super-P) and polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) in a mass ratio of 95%:2%:3%, and then an auxiliary agent was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on a 12μm aluminum foil, dried, cold pressed, and then cut and welded to the tabs to obtain the positive electrode.
[0198] The positive electrode active materials used in the examples or comparative examples were obtained from commercial sources, as shown in the following table:
[0199]
[0200] The additives used in the examples or comparative examples are shown in the following table:
[0201] Additives Name(Product Name) Oxidation potential Reduction potential Surface tension 1 2-Ethylhexyl acrylate 4.75V 0.1V 38mN / m 2 Acrylate nonionic fluorocarbon surfactant 4.8V 0.2V 35mN / m 3 Dodecyl methacrylate 4.7V 0.2V 38mN / m 4 Acrylic acid (ester) copolymer 4.8V 0.2V 36mN / m 5 Maleic Acid Acrylic Acid 4.7V 0.3V 37mN / m 6 Polyvinylpyrrolidone (abbreviated as PVP) 4.5V 0.1V 45mN / m 7 Polyether siloxane 4.7V 0.5V 45mN / m 8 Ping Ping Jia 4.6V 0.8V 47mN / m 9 Sodium hexadecyl sulfate 4.7V 0.7V 46mN / m
[0202] 3. Preparation of electrolyte
[0203] EC, PC, PP and DEC (weight ratio 1:1:1:1) were mixed under dry argon atmosphere, and LiPF 6 Mix well to form a basic electrolyte, in which LiPF 6 The concentration of the additive is 1.15 mol / L. Different amounts of additives are added to the basic electrolyte to obtain electrolytes of different embodiments and comparative examples.
[0204] The electrolyte components used in the examples are shown in the following table:
[0205] Material Name abbreviation Material Name abbreviation Ethylene carbonate EC Propylene carbonate PC Diethyl carbonate DEC Ethyl propionate EP Propyl Propionate PP γ-Butyrolactone GBL Succinonitrile SN Adiponitrile ADN Ethylene glycol di(2-cyanoethyl) ether EDN 1,3,6-Hexanetrinitrile HTCN 1,2,3-Tris(2-cyanoethoxy)propane TCEP Compound of formula 1 1a 1,3-Propane sultone PS Fluoroethylene carbonate FEC
[0206] 4. Preparation of isolation membrane
[0207] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0208] 5. Preparation of lithium-ion batteries
[0209] The obtained positive electrode, separator and negative electrode are wound in order and placed in an outer packaging foil, leaving a liquid injection port. The electrolyte is poured from the liquid injection port, packaged, and then subjected to formation, capacity and other processes to obtain a lithium-ion battery.
[0210] 2. Test Method
[0211] 1. Test method for contact angle of positive electrode active material layer relative to non-aqueous solvent
[0212] 3 microliters of diethyl carbonate was added to the surface of the positive electrode active material layer, and the JC2000D3E contact angle measuring instrument was used for testing within 100 seconds. The 5-point fitting method (i.e., first take 2 points on the left and right planes of the droplet to determine the liquid-solid interface, and then take 3 points on the arc of the droplet) was used for fitting to obtain the contact angle of the positive electrode active material layer relative to the non-aqueous solvent. Each sample was measured at least 3 times, and at least 3 data with a difference of less than 5° were selected, and the average value was taken to obtain the contact angle of the positive electrode active material layer relative to the non-aqueous solvent.
[0213] 2. Test method for the reaction area (Y) of the positive electrode active material layer
[0214] The sample was pre-dried at 350°C for 15 minutes under nitrogen flow using a surface area meter (fully automatic surface area measuring device manufactured by Okura Riken). Then, the specific surface area (m2) of the positive electrode active material layer was measured by the nitrogen adsorption BET single-point method using the gas flow method using a nitrogen-helium mixed gas whose relative pressure to atmospheric pressure was accurately adjusted to 0.3. 2 / mg). The reaction area (Y) of the positive electrode active material layer is calculated by the following formula:
[0215] Y=specific surface area of the positive electrode active material layer×weight of the positive electrode active material layer.
[0216] 3. Test method for capacity retention rate of lithium-ion batteries after cycling
[0217] At 45°C, the lithium-ion battery is charged to 4.45V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage of 4.45V, and then discharged to 3.0V at a constant current of 1C. This is the first cycle. The lithium-ion battery is cycled 200 times under the above conditions. "1C" refers to the current value that completely discharges the capacity of the lithium-ion battery within 1 hour. The capacity retention rate of the lithium-ion battery after cycling is calculated by the following formula:
[0218] Capacity retention rate after cycle = (discharge capacity after 200 cycles / discharge capacity at the first cycle) × 100%.
[0219] 4. Test method for rate performance of lithium-ion batteries
[0220] At 25°C, the lithium-ion battery was discharged to 3.0V at 0.2C and allowed to stand for 5 minutes. Then the lithium-ion battery was charged to 4.45V at 0.5C, and charged to 0.05C at 4.45V constant voltage, and allowed to stand for 5 minutes. The discharge rate was adjusted, and the discharge test was performed at 0.2C and 1.5C, respectively, to obtain the discharge capacity, and the ratio of the capacity obtained at 1.5C to the capacity obtained at 0.2C was recorded as the rate percentage.
[0221] 5. Test method of DC resistance (DCR) of lithium-ion battery
[0222] At 25°C, charge the lithium-ion battery to 4.45V at 1.5C constant current, then charge to 0.05C at 4.45V constant voltage, and let it stand for 30 minutes. Then discharge at 0.1C for 10 seconds, and record the voltage value as U1. Then discharge at 1C for 360 seconds, and record the voltage value as U2). "1C" is the current value that completely discharges the battery capacity within 1 hour. The DC impedance of the lithium-ion battery is calculated according to the following formula:
[0223] DC impedance = (U2-U1) / (1C-0.1C).
[0224] Unless otherwise specified, the DC impedance described in this application refers to the value of the lithium-ion battery at a state of charge (SOC) of 50%.
[0225] 3. Test Results
[0226] Table 1 shows the contact angle of the positive electrode active material layer relative to the non-aqueous solvent and the effect of the additive in the positive electrode active material layer on the performance of the lithium ion battery in each embodiment and comparative example. In each embodiment and comparative example shown in Table 1, the positive electrode active material is material 1, and the electrolyte contains 0.2wt% of the compound of formula 1a.
[0227] Table 1
[0228]
[0229] The results show that the additives and their content can affect the contact angle of the positive electrode active material layer relative to the non-aqueous solvent. Specific additives can increase the interaction between the components in the positive electrode active material slurry, making the slurry more evenly distributed, thereby reducing the contact angle of the positive electrode active material layer relative to the non-aqueous solvent. When the contact angle of the positive electrode active material layer relative to the non-aqueous solvent is not greater than 45°, the post-cycle capacity retention rate and rate percentage of the lithium-ion battery can be significantly improved, and the DC resistance of the lithium-ion battery can be significantly reduced. On the basis that the contact angle of the positive electrode active material layer relative to the non-aqueous solvent is not greater than 45°, controlling the content of the additive to be no more than 3000ppm can further improve the post-cycle capacity retention rate and rate percentage of the lithium-ion battery, and further reduce the DC resistance of the lithium-ion battery.
[0230] Table 2 shows the effect of positive electrode active materials on the performance of lithium ion batteries. The difference between Examples 11-15 and Example 3 is only the positive electrode active materials listed in Table 2.
[0231] Table 2
[0232] Positive active material Capacity retention after cycling Ratio Percentage DCR(mΩ) Example 3 Material 1 79% 77% 45 Embodiment 11 Material 2 82% 81% 34 Example 12 Material 3 85% 84% 32 Embodiment 13 Material 4 86% 85% 30 Embodiment 14 Material 5 81% 82% 37 Embodiment 15 Material 6 82% 85% 32
[0233] The results show that when the positive electrode active material includes lithium-containing transition metal oxides with different median particle sizes, the capacity retention rate and rate percentage of the lithium-ion battery after cycling can be further improved and its DC resistance can be further reduced. When the lithium-containing transition metal oxide contains Mg and at least one metal element selected from Ti, Zr, Ge, Nb, Al and Sn, the improvement of the cycling performance, rate performance and DC resistance of the lithium-ion battery is particularly obvious.
[0234] Table 3 shows the effect of the content of the compound of formula 1a in the electrolyte on the performance of the lithium ion battery. The difference between Examples 16-22 and Example 3 is only the parameters listed in Table 3.
[0235] Table 3
[0236] 1a content (wt%) Capacity retention after cycling Ratio Percentage DCR(mΩ) Example 3 0.2 79% 77% 45 Example 16 0.5 85% 83% 26 Embodiment 17 1 86% 87% 23 Embodiment 18 2 80% 81% 29 Embodiment 19 0.001 71% 75% 38 Embodiment 20 0.005 72% 80% 36 Embodiment 21 0.0008 66% 71% 49 Embodiment 22 3 70% 68% 51
[0237] The results show that when the content of the compound of formula 1a in the electrolyte is in the range of 0.001wt% to 2wt%, the cycle performance, rate performance and DC resistance of the lithium-ion battery can be further significantly improved. The difference between formula 1b and formula 1c and formula 1a is only in the carbon chain length, and they can achieve the same effect as formula 1a.
[0238] Table 4 shows the effect of the relationship between the weight of the compound of Formula 1 and the reaction area of the positive electrode active material layer on the performance of the lithium ion battery. The difference between Examples 23-26 and Example 3 is only the parameters listed in Table 4.
[0239] Table 4
[0240]
[0241] The results show that when the content of the compound of formula 1 in the electrolyte is X mg and the reaction area of the positive electrode active material layer is Ym 2 When 10≤X / Y≤100 is satisfied, it helps to further improve the cycle performance, rate performance and DC resistance of lithium-ion batteries.
[0242] Table 5 shows the effect of the additives in the electrolyte on the performance of the lithium ion battery. The difference between Examples 27-34 and Example 3 is only the parameters listed in Table 5.
[0243] Table 5
[0244]
[0245] The results show that when the electrolyte further contains additives, it helps to further improve the cycle performance, rate performance and DC resistance of lithium-ion batteries.
[0246] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.
[0247] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. An electrochemical device comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode active material layer, wherein the contact angle of the positive electrode active material layer relative to a non-aqueous solvent is not greater than 45° as measured by a contact angle measurement method; The electrolyte comprises a compound of formula 1, and the compound of formula 1 comprises at least one of the following structural formulas:
2. The electrochemical device according to claim 1, wherein the contact angle measurement method is to drop a 3 μl drop of diethyl carbonate on the surface of the positive electrode active material layer and then measure the contact angle of the drop on the surface of the positive electrode active material layer within 100 seconds. 3 . The electrochemical device according to claim 1 , wherein the positive electrode active material layer comprises an auxiliary agent having a hydrophilic group and a lipophilic group.
4. The electrochemical device according to claim 3, wherein the auxiliary agent has at least one of the following characteristics: (a) The oxidation potential is not less than 4.5 V and the reduction potential is not greater than 0.5 V; (b) The surface tension is not greater than 40 mN / m; (c) comprising an unsaturated carboxylic acid group; (d) The content of the auxiliary agent is not more than 3000 ppm based on the total weight of the positive electrode active material layer.
5. The electrochemical device according to claim 3, wherein the auxiliary agent comprises at least one of 2-dodecyl acrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate, acrylate (2-ethylhexyl) ester, acrylate nonionic fluorocarbon surfactant, dodecyl methacrylate, acrylic acid (ester) copolymer, maleic acid acrylic acid copolymer or ethylene acrylic acid copolymer.
6. The electrochemical device according to any one of claims 1 to 5, wherein the content of the compound of formula 1 is 0.001 wt% to 2 wt% based on the total weight of the electrolyte.
7. The electrochemical device according to any one of claims 1 to 5, wherein the content X mg of the compound of Formula 1 in the electrolyte and the reaction area Y m of the positive electrode active material layer 2 The following relationship is satisfied: 10≤X / Y≤100. 8 . The electrochemical device according to claim 1 , wherein the positive electrode active material layer comprises a positive electrode active material comprising a lithium-containing transition metal oxide having different median particle sizes.
9. The electrochemical device according to claim 8, wherein the lithium-containing transition metal oxide comprises a compound represented by the general formula (1), <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> M1<h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> c <h2 style=";text-align:left;direction:ltr"> M3<h2 style=";text-align:left;direction:ltr"> d <h2 style=";text-align:left;direction:ltr"> O2(1) in: M1 is selected from at least one of Co, Ni or Mn; M2 is at least one selected from Mg, Ti, Zr, Ge, Nb, Al or Sn; M3 is an element other than Li, M1 and M2; 0.5≤a<1.1; 0.8≤b<1.2; 0.002≤c≤0.05; and 0≤d≤0.05。 10. The electrochemical device according to claim 8 or 9, wherein the lithium-containing transition metal oxide comprises Mg and at least one metal element selected from the group consisting of Ti, Zr, Ge, Nb, Al and Sn.
11. An electronic device comprising the electrochemical device according to any one of claims 1 to 10.